Recovery of the historical SN1957D in X-rays with Chandra - Long, K.; Blair, W.; Godfrey, Leith; Kuntz, K.; Plucinsky, P.; Soria, Roberto; Stockdale, C.; Whitmore, B.; Winkler, P. (Institute of Physics Publishing, Inc., 2012)
SN1957D, located in one of the spiral arms of M83, is one of the small number of extragalactic supernovae (SNe) that has remained detectable at radio and optical wavelengths during the decades after its explosion. Here, we report the first detection of SN1957D in X-rays, as part of a 729 ks observation of M83 with Chandra. The X-ray luminosity (0.3-8 keV) is 1.7+2.4 – 0.3 × 1037 erg s–1. The spectrum is hard and highly self-absorbed compared to most sources in M83 and to other young supernova remnants (SNRs), suggesting that the system is dominated at X-ray wavelengths by an energetic pulsar and its pulsar wind nebula. The high column density may be due to absorption within the SN ejecta. Hubble Space Telescope WFC3 images resolve the SNR from the surrounding emission and the local star field. Photometry of stars around SN1957D, using WFC3 images, indicates an age of less than 107 years and a main-sequence turnoff mass more than 17 M ☉. New spectra obtained with Gemini-South show that the optical spectrum continues to be dominated by broad [O III] emission lines, the signature of fast-moving SN ejecta. The width of the broad lines has remained about 2700 km s–1 (FWHM). The [O III] flux dropped precipitously between 1989 and 1991, but continued monitoring shows the flux has been almost constant since. In contrast, radio observations over the period 1990-2011 show a decline rate S ν ~ t –4.0, far steeper than the rate observed earlier, suggesting that the primary shock has overrun the edge of a pre-SN wind.